The wind from the east : French intellectuals, the cultural revolution, and the legacy of the 1960s - Wolin, Richard (Princeton, New Jersey : Princeton University Press : Princeton University Press, 2018)
Combining a merciless exposé of left-wing political folly and cross-cultural misunderstanding with a spirited defense of the 1960s, this book tells the colourful story of this legendary period in France.
Part I. The hour of rebellion. Showdown at Bruay-en-Artois -- France during the 1960s -- May 1968 : the triumph of libidinal politics -- Who were the Maoists? -- Excursus : on the sectarian Maoism of Alain Badiou -- Part II. The hour of the intellectuals. Jean-Paul Sartre's perfect Maoist moment -- Tel quel in cultural-political hell -- Foucault and the Maoists : biopolitics and engagement -- The impossible heritage : from cultural revolution to associational democracy.
Online resource; title from PDF title page (Ebsco, viewed October 25, 2017).
Includes bibliographical references and index.
JSTOR
Keywords: Mao, Zedong, -- 1893-1976 -- Influence; Mao, Zedong, -- 1893-1976; Intellectuals -- France -- History -- 20th century; Intellectuals -- Political activity -- France -- History -- 20th century; France -- Intellectual life -- 20th century; Communism -- France -- History -- 20th century; China -- History -- Cultural Revolution, 1966-1976 -- Influence; Intellectuels -- France -- Histoire -- 20e siècle.; Intellectuels -- Activité politique -- France -- Histoire -- 20e siècle.; France -- Vie intellectuelle -- 20e siècle.; Chine -- Histoire -- 1966-1976 (Révolution culturelle) -- Influence; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; HISTORY -- Europe -- France; Communism; Influence (Literary, artistic, etc.); Intellectual life; Intellectuals; Intellectuals -- Political activity; China; France; 1900-1999; History